The Effect of Auditory Verbal Hallucinations on the Relationship between Spontaneous Brain Activity and intraventricular Brain Temperature in Patients with Drug-Naïve Schizophrenia. (11th June 2020) - Zhao, Zhiyong; Xu, Guojun; Shen, Zhe; Grunebaum, Michael; Li, Xuzhou; Sun, Bin; Li, Shangda; Xu, Yi; Huang, Manli; Xu, Dongrong
Highlights: Schizophrenia patients with auditory verbal hallucinations (AVH) showed altered coupling between intraventricular brain temperature (iBT) and spontaneous brain activity (SBA), compared with both non-AVH schizophrenia patients and healthy controls. Differences of iBT were insignificant among the three groups. AVH may modulate the relationship between iBT and SBA in several schizophrenia-related regions in the brain. Abstract: Our recent study reported that adolescent-onset schizophrenia showed an uncoupling between intraventricular brain temperature (iBT) and local spontaneous brain activity (SBA). While auditory verbal hallucinations (AVH) are common in schizophrenia, the role of AVH in the iBT-SBA relationship is unclear. The current study recruited 24 drug-naïve schizophrenia patients with AVH, 20 patients without AVH and 30 matched healthy controls (HC). We used a diffusion-weighted imaging (DWI) based thermometry method to calculate the iBT for each participant and used both regional homogeneity and amplitude of low-frequency fluctuation methods to assess the SBA. One-way ANOVA was used to detect group differences in iBT, and a partial correlation analysis controlling for lateral ventricles volume, sex and age was applied to detect the relationships between iBT and SBA across the three groups. The results demonstrated that the AVH group showed a significant coupling between iBT and SBA in the bilateral lingual gyrus, left superior occipital gyrus and caudate compared with the other two groups, and no uncoupling was found in the two patients groups relative to HCs. These findings suggest that AVH may modulate the relationship between iBT and SBA in schizophrenia-related regions.